Motivation Influences Nurses' Performance at Mutiara Aini Hospital Batam - Rifelita Saputra; Ismail Efendy; Ramadhani Syafitri Nasution (Universitas Ibn Khaldun Bogor, 2026)
Motivation is a key internal factor that drives individuals to act and achieve specific goals. In healthcare settings, nurses play a critical role in ensuring the quality of hospital services through both clinical care and patient support. This study aimed to analyze the effect of motivational factors on nurses’ performance at Mutiara Aini Hospital, Batam City. A quantitative study with a cross-sectional design was conducted involving 79 nurses selected using total sampling. Data were collected through structured questionnaires, interviews, and observations, and analyzed using multiple logistic regression with a significance level of α = 0.05. The results showed that achievement (p = 0.023), recognition (p = 0.048), personal growth (p = 0.013), interpersonal relationships (p = 0.040), and supervision (p = 0.027) significantly influenced nurses’ performance. Among these variables, supervision was identified as the most dominant factor, with an Exp(B) value of 654.732. In conclusion, both intrinsic and extrinsic motivational factors significantly affect nurses’ performance. Strengthening supervisory practices is essential to improve nurse performance and overall healthcare service quality.